One-pot synthesis of gold nanodimers and their use as surface-enhanced Raman scattering tags. (27th July 2016) - Vilar-Vidal, Noelia; Bonhommeau, Sébastien; Talaga, David; Ravaine, Serge
Abstract : Gold dimers consisting of 40 nm-diameter nanospheres show enhancement factors as high as ∼1.8 × 10 7 at the hot-spot level. Abstract : A simple one-pot method to synthesize, with reasonably high yields, gold nanodimers consisting of 40 nm-diameter nanospheres is described. Colocalized Rayleigh and surface-enhanced Raman scattering measurements on individual dimers suggest a relatively narrow distribution of interparticle gaps and demonstrate enhancement factors as high as ∼1.8 × 10 7 at the hot-spot level.